Planejamento anual da operação de controle de cheias em aproveitamentos hidroelétricos: estudo da estacionariedade hidrológica - Chan, Priscilla Dafne Shu (2020)
During the rainy season, the Brazilian Power Sector reserves empty volumes in its hydropower reservoirs, referred to as the so-called waiting volume, in order to dampen potential floods that might occur. The currently used flood control methodology is based on the assumption of the stationarity of the naturalized daily streamflow time series and also allows the consideration of the phenomenon ENSO (El Niño South-Oscillation). Given the possibility of changes in the hydrological cycle, studies have been carried out in order to evaluate possible alterations, which are already identifiable in the historical series. In this context, it is proposed a methodological approach for the analysis of stationarity of maximum annual streamflow series of duration compatible with flood events focusing on flood control associated to hydropower reservoirs. The procedure considered the analysis of temporal stationarity directly and indirectly, the last through the study of temporal variations of the ENSO phenomenon. The results of such procedure applied to the Paraná river basin until Porto São José fluviometric station, by means of considering maximum annual inflows of 10-days averages, suggest that the Paraná river basin until Jupiá presents a temporal stationary behavior, while the Paranapanema river basin reveals a non-stationary behavior. In general, it can be said that the flood regime in the Paraná river basin is influenced by ENSO.